Faktor Diterminan Penyampaian Laporan Keuangan - Majidah Majidah; Intan Aisah (Owner : Riset dan Jurnal Akuntansi, 2023)
Companies listed on the Indonesia Stock Exchange are obliged to submit financial statements to the Financial Services Authority (OJK) at any time. However, there are still around 25.1% of companies that do not timely submit their financial statements. This condition results in financial statements losing their relevant meaning because they cannot be utilized by potential investors for decision-making. The study proposes to examine the factors that affect the timeline of financial statement submission. The object of this research is consumer cyclical sector companies for the 2017–2021 period. Based on several criteria in determining the sample, 70 company samples, or 350 data points, were obtained. Analysis of research data using logistic regression panel data using Stata 17. The results showed that corporate governance, CEO tenure, complexity of company operations, and financial difficulties simultaneously affect the timeliness of financial statement submission. Nevertheless, corporate governance, the tenure of the CEO, and the complexity of the company's operations each negatively affect the timeliness of financial statement submission. Corporate governance proxy using the Governance Item Checklist is a novelty of this research. It is recommended that the next researcher conduct research again on the consumer noncyclical sector on the Indonesia Stock Exchange.